Spomin in identiteta v romanu Očeta Vincenca smrt Petra Božiča - Vollmaier Lubej, Janja (Ars et humanitas, 2018)
Th e article deals with a novel by the contemporary Slovenian writer Peter Božič (1932-2009). It presents traumatic war experiences, death experiences and the question of identity formation, and the issue of memory plays a key role in this. Th e articles discusses the literary texts of Peter Božič and an interpretation of the novel The Death of Father Vincent, with an emphasis on its stylistic, linguistic, and thematic aspects. Th e article also presents the memory of a boy An, his identity and the identities of other characters. It is established that the novel shows the intertwining of individual and collective memory, and also the absence of identity because of past trauma.
Keywords: Božič, Peter; collective memory; identiteta; identity; individual memory; individualni spomin; kolektivni spomin; roman; Slovene literature; slovenska književnost; trauma; travma